Strong convergence of an iterative algorithm involving nonlinear mappings of nonexpansive and accretive type - Qin, Xiaolong; Cho, Sun Young; Wang, Lin (Optimization, 2018)
In this paper, a new iterative method for finding the projection onto the intersection of two closed convex sets in the framework of Banach spaces is presented. It is a viscosity approximation method which produces a strongly convergent sequence.